INVENTORY PLANNING ANALYSIS OF RAW MATERIALS FOR ANIMAL FEED USING THE MRP LOT SIZING TECHNIQUE AT CV. XYZ - rahmawati, nur; Dean Tirkaamiana (Program Studi Teknik Industri Universitas Pembangunan Nasional Veteran Jawa Timur, 2025)
Material Requirement Planning (MRP) is a system used to organize and supervise production chain management, with the aim of managing the inventory of raw materials, components, and finished products in the manufacturing or production process. CV. XYZ has problems related to production delays caused by lack of raw material inventory. This study aims to ensure the right ordering schedule and minimize ordering costs at CV. XYZ by using the MRP method and lot sizing techniques, where the lot sizing techniques used are Least Unit Cost (LUC) and Least Total Cost (LTC). Based on the results of MRP calculations using the Least Unit Cost lot sizing technique, the total cost is Rp2,235,127 while the MRP method with Least Total Cost is Rp. 1,936,651. Thus, the MRP method with Least Total Cost has a smaller total cost than Least Unit Cost, so this is an effective solution in planning the inventory of animal feed raw materials at CV. XYZ.